ANALISA PERBANDINGAN KNALPOT STANDAR DAN KNALPOT FREE FLOW TERHADAP PERFORMA MESIN 4 LANGKAH 155 CC - Satrio Galuh Dewanto; Ranto Ranto; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
Motor performance is one of the things that must be considered in motorized vehicles. Motor performance also influences the type of exhaust system, namely the muffler. Many people don't know how big the influence of the exhaust free flow on engine performance. In this study using Yamaha Nmax Old 2016. The aims of this study were: (1) To find out the difference in torque and power produced by a motorbike between the use of a standard NMAX 155 CC exhaust and a standard exhaust free flow. (2) Knowing the difference in fuel consumption produced by motorcycles between the use of a standard NMAX 155 CC exhaust and exhaust free flow. (3) Knowing the difference in exhaust emissions produced by motorbikes between the use of the standard NMAX 155 CC exhaust and the exhaust free flow. The research method used is experimental. The data for this study were obtained by measuring a sample of the Yamaha NMAX Old 2016 motorcycle. The independent variables were the standard exhaust and the exhaust free flow. The dependent variables are torque, power, fuel consumption and exhaust emissions. The data obtained were then analyzed using quantitative descriptive techniques by describing them in the form of graphs and tables. The results of this study are: (1) Use of Muffler free flow has a lower effect on the torque and power generated by the Yamaha NMAX Old 2016 motorcycle. (2) Use of Muffler free flow has a higher effect on fuel consumption produced by Yamaha NMAX Old 2016 motorbikes. (3) Use of Muffler free flow has an influence on increasing levels of exhaust emission content produced by Yamaha NMAX Old 2016 motorbikes.